THE FEATURES OF PHRASEOLOGICAL SYNONYMIC ROWS OF ENGLISH AND UZBEK LANGUAGES - Gulbar Rizokulovna Sanoyeva (Web of Journals Publishing, 2024)
This article supplies us with the data about figurative, stylistic coloring of phraseological synonymic rows of English and Uzbek languages.
Keywords: Phrase, synonymic rows, lexical, language, meaning, a word.